Investigação de polimorfismos nos genes IFNɣ e INFGR1 associados à tuberculose no estado do Pará - CARNEIRO, Klezzer de Oliveira (Universidade Federal do Pará, 2017)
Pulmonary tuberculosis is an infectious disease transmission by air, which according to the World Health Organization (WHO), infects about two billion people around the world. It is the leading cause of death from infectious disease in adults in developing countries, representing a serious public health problem, mainly due to non-adherence to treatment, late diagnosis and underdiagnosis and no control contacts, which makes our population susceptible to infection. The present study aimed to investigate associations three genetic polymorphisms in IFNɣ and INFGR1 genes responsible for susceptibility to tuberculosis in patients affected by the disease; evaluate if there are differences in allelic and genotypic frequencies of polymorphisms in genes IFNɣ 871A> T, INFGR1 611 (C> T) and INFGR1 -56 (A> G) among individuals with TB and those without TB population of Bethlehem. The control substructures effect was carried out by the use ofa 48 markers Informational Genetic Ancestry panel in both patient sample and the control sample. For this study we used peripheral blood samples from 148 patients diagnosed with tuberculosis, and 125 individuals without tuberculosis (controls) resident in the State of Pará, Brazil, attended at University Hospital João de Barros Barreto (HUJBB) during the period from 2006 to 2012. each specimen was obtained 5 ml of venous blood collected from a peripheral vein. DNA extraction was performed according to the method described by Sambrook et al., (1989). Genotyping for polymorphisms IFNɣ gene (rs1130562) and INFGR1 (rs1327474, rs2234711) was performed by PCR in real time (RTQ-PCR) using the TaqMan system. Statistical analyzes were performed in SPSS 17.0 software, using the Mann- Whitney test, with significance set at p <0.05. The results did not show significance of the polymorphisms investigated in relation to susceptibility to tuberculosis.